Super-electrophiles of tri- and tetra-anions stabilized by selected terminal groups and their role in binding noble gas atoms. Issue 38 (23rd July 2021) - Zhong, Ming Min; Fang, Hong; Deepika,; Jena, Puru
Abstract : Stabilization of multiply-charged clusters in the gas phase has been a topic of great interest not only because of their potential applications as weakly-coordinating anions, but also for their ability to promote unusual reactions. Abstract : Stabilization of multiply-charged atomic clusters in the gas phase has been a topic of great interest not only because of their potential applications as weakly-coordinating anions, but also for their ability to promote unusual reactions and serve as building blocks of materials. Recent experiments have shown that, after removing one terminal ligand from the closo -dodecacyano-borate, B12 (CN)12 2−, the cluster can strongly bind an argon atom at room temperature. Bearing this in mind, here, we have developed more than a dozen highly stable tri- and tetra-anions using density functional theory (DFT) calculations with hybrid functional (B3LYP) and semi-empirical dispersion corrections. The interactions between the clusters and noble gas atoms, including Ne, Ar and Kr, are studied. The resulting super-electrophilic sites embedded in these charged clusters can bind noble gas atoms with binding energies up to 0.7 eV. This study enriches the database of highly-charged clusters and provides a viable design rule for super-electrophiles that can strongly bind noble gas atoms.